The application of additive technologies in the surgical treatment of chronic pelvic injuries using original plates - Ya. G. Gudushauri; A. F. Lazarev; E. I. Solod; E. I. Kalinin; V. V. Konovalov; I. N. Marychev; N. M. Kakabadze (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. Modern technologies for 3D printing of implants for surgical treatment of patients are actively introduce into the medical field. Chronic injuries of the pelvis are an actual problem in traumatology and orthopedics, and the use of the developed original metal structure in conjunction with additive technologies will improve the results of treatment in male and female patients, as it allows creating adapted designs, taking into account the morphology of an individual patient. The OBJECTIVE was to create the adapted design taking into account anatomical features for stable fixation pelvic bones in each individual patient using modern additive technologies and to compare the results of treatment using a serial polyposition plate and an individual plate. METHODS AND MATERIALS. We carried out a comparative analysis of the results of treatment in the study groups. Group ¹ 1 consisted of patients with fixation of the anterior pelvis with polyposition plate, group ¹ 2 – fixation with individual reconstructive plate. RESULTS. We used computed tomography of the female pelvis. A virtual 3D reconstruction of the female pelvis was performed and the original reconstructive plate was modeled taking into account the morphology of the anterior pelvis in a particular case. After sending the results of computed tomography and agreeing on the plate model and its position, a finished titanium original metal structure was obtained. The total period from the CT examination to the manufacture of the plate was 8 days. In the studied groups, the number of destabilizations was: in group ¹ 1 – 6.6 %, in group ¹ 2 – 0 %. CONCLUSION. The use of additive technologies in the manufacture of metal structures allows creating the adapted design for a particular patient, taking into account his morphology. The use of metal structures using 3D printing technology will improve the results of treatment of patients with chronic pelvic injuries and reduce the number of destabilizations. The short time required for modeling and creating the adapted metal structure allows patients to receive the necessary medical care as soon as possible.